Study on Degradation of Leaf Litter of Five Tree Species by Perionyx excavatus with Relation to Their Nutrient and Anti-nutrient Content - Pattanayak, Sayantani; Dasgupta, Rupa; Chakravorty, Partha Pratim; Chakraborty, Susanta Kumar (Research Aspects in Agriculture and Veterinary Science Vol. 2, 2021)
The ecological suitability of different leaf litter types in enhancing the biological diversity and micronutrient status in soil needs to be understood for deciding the plant species to be used for afforestration practices. The present research work was done to study the colonization of an epigeic earthworm, Perionyx excavatus in the decomposing leaf litter of five locally important tree species- Cashew, Shal, Mango, Acacia and Eucalyptus up to a period of 90 days. The major nutrient and anti-nutrient chemical parameters of the leaf litters were compared and rates of degradation of the selected nutrient and anti-nutrient parameters were studied in laboratory microcosms. P. excavatus showed maximum colonization for Cashew followed by Shal where both these tree species exhibited comparatively lower anti-nutrient content and significantly higher rates of degradation of the selected nutrient parameters. Lowest colonization by P. excavatus was observed in case of Eucalyptus which exhibited highest polyphenol and tannin content and significant lower rates of degradation of all the selected nutrient parameters and hence their utilization in microcosms with P. excavatus. The results indicated that lower content of tannins and polyphenols in case of Cashew and Shal can be related to the palatability of these leaf litters and thereby exhibiting maximum colonization by P. excavatus. Thus, Cashew and Shal can be considered as suitable tree species for afforestation practices for enhancing nutrient recycling and effective soil conservation.